Mobile Computing Solutions for Healthcare Systems - Sivakumar R.; Velev, Dimiter; Alhadidi, Basim; Vidhya, S.; V. Francis, Sheeja; Prabadevi, B. (Bentham Science Publishers, 2023)
This book focuses on recent developments in integrating AI, machine learning methods, medical image processing, advanced network security, and advanced antenna design techniques to implement practical Mobile Health (M-Health) systems. The editors bring together researchers and practitioners who address several developments in the field of M-Health. Chapters highlight intelligent healthcare IoT and Machine Learning based systems for personalized healthcare delivery and remote monitoring applications. The contents also explain medical applications of computing technologies such as Wireless Body Area Networks (WBANs), wearable sensors, multi-factor authentication, and cloud computing. The book is intended as a handy resource for undergraduate and graduate biomedical engineering students and mobile technology researchers who want to know about the recent trends in mobile health technology.